O3-Induced Leaf Senescence in Tomato Plants Is Ethylene Signaling-Dependent and Enhances the Population Abundance of Bemisia tabaci - Guo, Honggang; Sun, Yucheng; Yan, Hongyu; Li, Chuanyou; Ge, Feng (Frontiers in Plant Science, 2018)
Elevated O3 can alter the phenotypes of host plants particularly in induction of leaf senescence, but few reports examine the involvement of phytohormone in O3-induced changes in host phenotypes that influence the foraging quality for insects. Here, we used an ethylene receptor mutant Nr and its wild-type to determine the role of the ethylene signaling pathway in O3-induced leaf senescence, and bottom-up effects on the performance of Bemisia tabaci in field open top chambers (OTCs). Our results showed that elevated O3 reduced photosynthetic efficiency and chlorophyll content and induced leaf senescence of plant regardless of plant genotype. Leaf senescence in Nr plants was alleviated relative to wild-type under elevated O3. Further analyses of foliar quality showed that elevated O3 had little effect on phytohormone-mediated defenses, but significantly increased the concentration of amino acids in two plant genotypes. Furthermore, Nr plants had lower amino acid content relative to wild-type under elevated O3. These results provided an explanation of O3-induced increase in abundance of B. tabaci. We concluded that O3-induced senescence of plant was ET signal-dependent, and positive effects of O3-induced leaf senescence on the performance of B. tabaci largely resulted from changes of nutritional quality of host plants.